What can we say about substance use? Dominant discourses and narratives emergent from Australian media - Bright, S.; Marsh, A.; Smith, Leigh; Bishop, Brian (Taylor & Francis, 2008)
Discourses are conceptualised as context-specific frameworks that constrain what can be presented as rational when considering psychoactive substances. Given the implications of this for Australian policy debate and development, research and health promotion, an integrative analysis explored the nature of the dominant discourses as they pertain to substance use. Newspaper articles spanning a 12-month period (April 2005 2006) were analysed with the analysis triangulated with visual media and newspapers from 5-years prior. We conclude that within Australia, psychoactive substance use is framed within the dominant discourses of medicine, morality, law, economics, politics and popular culture. The linguistic landscape circumscribed by each discourse is described and the power dynamics underpinning the maintenance of the discourses considered, with each discursive framework shown to delineate unique subject positions that define the numerous individuals concerned with substance use issues (e.g. substance users, politicians, medical experts, etc.).